PENGARUH BAGI HASIL AKAD MUDHARABAH TERHADAP KEPUASAN NASABAH PADA BANK ACEH CAPEM KUTABLANG (Studi Kasus Nasabah Di Kecamatan Kutablang) - Hidayatullah Munzir; Aulia Fitri (Jurnal Syariah dan Ekonomi Islam, 2024)
The development of the Islamic banking system in Indonesia is carried out within the framework of the dual banking system or dual banking system within the framework of the Indonesian Banking Architecture (API) to present an increasingly complete alternative banking service to the Indonesian people. Contracts or agreements in people's lives occupy a very important position. Akad is one of the foundations of many daily human activities. Through contracts, various business activities and human efforts can be carried out. Because the contract is what limits the relationship between the two parties involved in the business and will bind the relationship in the present and the future. The method used in this study is a quantitative research method. The variables of the research are Akad Mudharabah (X) and Customer Satisfaction (Y). The data collection technique was carried out through a questionnaire, the sample taken amounted to 72 respondents using an incidental sampling technique. The analysis tools used IBM SPSS Statistics 23 which included validity tests, reliability tests, classical assumption tests, T hypothesis tests, linear regression analysis. The results of the study show that the Mudharabah Akad has an effect on customer satisfaction at PT. Bank Aceh Syariah Capem Kutablang, this can be seen from the results  of the calculation value of Akad Mudharabah on customer satisfaction of 8,888 with a significant 0.001 < 0.05, while the ttable value is 1,666 < 8,888 tcal. So the value of t calculation is greater than the t table, this shows that Ho was rejected and accepted by Ha who stated that the Mudharabah Contract had a significant influence on Customer Satisfaction at PT. Bank Aceh Syariah Capem Kutablang.